The face mask in COVID times a sociomaterial analysis - Lupton, Deborah 1963-; Southerton, Clare ca. 20. Jh; Clark, Marianne ca. 20. Jh; Watson, Ash ca. 20. Jh (De Gruyter, 2021)
The simple fabric face mask is a key agent in the fight against the global spread of COVID-19. However, beyond its role as a protective covering against coronavirus infection, the face mask is the bearer of powerful symbolic and political power and arouses intense emotions. Adopting an international perspective informed by social theory, The Face Mask in COVID Times: A Sociomaterial Analysis offers an intriguing and original investigation of the social, cultural and historical dimensions of face-masking as a practice in the age of COVID. Rather than Beck's 'risk society', we are now living in a 'COVID society', the long-term effects of which have yet to be experienced or imagined. Everything has changed. The COVID crisis has generated novel forms of sociality and new ways of living and moving through space and time.
Keywords: COVID-19; Maskengegner; Mund-Und-Nasenschutz; Mundschutz; Soziologie; SOCIAL SCIENCE / Sociology / General; Mund-Nasen-Schutz; Pandemie; Wandel; Gesellschaft; Alltag